A novel study of situational awareness among out-of-hospital providers during an online clinical simulation. (March 2023) - Hunter, Justin; Porter, Michael; Williams, Brett
Abstract: Background: Out-of-hospital providers must be situationally aware in order to maintain safety for themselves, their patients, the public, and their crew. They must be able to recognize situations, interpret them, and predict how those situations may unfold in the future. Method: A mixed-methods explanatory sequential design where out-of-hospital providers in Oklahoma, USA, participated in an 18-minute online simulation and then had their situational awareness (SA) measured. Upon completion, participants provided feedback during scheduled interviews. Results: A total of 156 out-of-hospital providers participated. Participants were not situationally aware. While not statistically significant, those with higher education had higher SA scores. Participants perceived that the simulation processes were beneficial to their ongoing care in the field, and were satisfied with the online simulation environment. Conclusions: Out-of-hospital providers are not situationally aware during an online clinical simulation. While they are focused intently on the surroundings of the scene, they do not put that same focus on the patient. With the appropriate technology and setup, the use of the Situational Awareness Global Assessment Technique (SAGAT) during online simulation is feasible and could enhance clinical performance. Further studies are needed to determine if overall education or years of clinical experience play a role in out-of-hospital SA.